Final report on industrial attachment with Renewable Energy Corporation Pte Ltd - Ye, Peiru. (2012)
Inline sheet resistance (SHR) measuring tool is ideally plugged in the unloading section of the diffusion furnace in order to show systematic drifts and give immediate feedback on dramatic process changes. However, there is an uncertainty in the accuracy of the inline tool. First half of the report discusses how this inline tool can be fully utilized by using the offline SHR measuring tool- four point probe as a cross-reference source.